2018
DOI: 10.1371/journal.ppat.1007424
|View full text |Cite
|
Sign up to set email alerts
|

Prion pathogenesis is unaltered in a mouse strain with a permeable blood-brain barrier

Abstract: Transmissible spongiform encephalopathies (TSEs) are caused by the prion, which consists essentially of PrPSc, an aggregated, conformationally modified form of the cellular prion protein (PrPC). Although TSEs can be experimentally transmitted by intracerebral inoculation, most instances of infection in the field occur through extracerebral routes. The epidemics of kuru and variant Creutzfeldt-Jakob disease were caused by dietary exposure to prions, and parenteral administration of prion-contaminated hormones h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Mice. Previous studies have shown a negative correlation between pericyte coverage and BBB permeability in the brain (1,2,(17)(18)(19). We therefore asked whether selective leukocyte infiltration into different CNS regions in Pdgfb ret/ret mice can be explained by differences in capillary pericyte coverage in the brain and spinal cord.…”
Section: Spatial Differences In Pericyte Coverage In the Cns Of Pdgfbmentioning
confidence: 92%
“…Mice. Previous studies have shown a negative correlation between pericyte coverage and BBB permeability in the brain (1,2,(17)(18)(19). We therefore asked whether selective leukocyte infiltration into different CNS regions in Pdgfb ret/ret mice can be explained by differences in capillary pericyte coverage in the brain and spinal cord.…”
Section: Spatial Differences In Pericyte Coverage In the Cns Of Pdgfbmentioning
confidence: 92%
“…The rate of onset can be accelerated in models in which SLOs are hyperinnervated or where FDCs are juxtaposed to splanchnic nerves (Glatzel et al, 2001). The critical role of retrograde transport of prions has been corroborated via studies showing that disruption of the BBB does not impact pathogenesis (Keller et al, 2018) Conclusions: Can Pathogens Teach Us How to Deliver Therapeutics into the CNS? This review describes CNS entry mechanisms utilized by intracellular and extracellular pathogens.…”
Section: Axonal Transport From Peripheral Neuronsmentioning
confidence: 99%
“…Previous studies have shown a negative correlation between pericyte coverage and BBB permeability in the brain 1, 2, 1416 . We therefore asked whether selective leukocyte infiltration into the brain in Pdgfb ret/ret (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 88%